Adjusting unit cell three-dimensional posture and mirror array: A novel lattice structure design approach. (September 2022) - Chen, Xiaohong; Ren, Wenxin; Sun, Yuanxi; Zhang, Junfang; Yang, Jianxing; Wang, Ke; Gong, Yu; Zhang, Zhiqing; Bai, Long
Graphical abstract: Highlights: Proposed a lattice structure design approach that generates predictable mechanical properties by adjusting the three-dimensional posture and mirror arrays of cells. Investigated relative density, quasi-static compression response and energy absorption characteristics of titanium alloy lattice structures with different Euler Angles. Proposed a method combining coordinate positioning and datum cutting to accurately predict the relative density of the models. Abstract: Lattice structures' performance is directly determined by the topological structure and arrangement of cells. Here, we propose a lattice structure design approach that generates predictable mechanical properties by adjusting the three-dimensional posture and mirror arrays of cells. Specifically, the Euler angle ( α β γ ) is introduced to accurately control the three rotational degrees of freedom of the orthogonal unit cell. Then, a new unit cell with symmetric characteristics composed of multiple primitive rotation units is constructed by mirror operation, which is called super variable pose Octahedral Structures (SVPOS). The mathematical model of SVPOS topological structure is established, the mapping relationship between Euler Angle and relative density is deduced, and the mechanical response of structures with different Euler angles is studied. The results show that Structure of α = β = γ = 30˚ obtained the best performance, and the elastic modulus, compressive strength, and energy absorption at 50% strain of it are 553.1%, 471.9% and 529% of that of the octahedral, respectively. The new lattice structure can be obtained by adjusting the Euler Angle, its relative density and performance can be better predicted, which can provide experimental and theoretical basis for the design of lattice structures that meet different requirements.